DEVELOPMENT OF A NEW METHOD FOR DIAGNOSIS OF COXSACKIE B5 VIRUSES BY REVERSE TRANSCRIPTION LOOP-MEDIATED ISOTHERMAL AMPLIFICATION - K.JAIANAND; P.GUNASEKARAN; M.RAJKUMAR; A.K.SHERIFF (International Journal of Pharma and Bio Sciences, 2010)
We developed a one-step, single-tube genogroup-specific reverse transcription–loop-mediated isothermal amplification (RT-LAMP) assay for the detection of group B Coxsackie genomes targeting 5’ UTR region. The amplification can be obtained in less than 1 h by incubating all of the reagents in a single tube with reverse transcriptase and Bst DNA polymerase at 63°C. Detection of gene amplification could be accomplished by agarose gel electrophoresis, as well as , the monitoring of gene amplification can also be visualized with the naked eye by using SYBR green I fluorescent dye. A total of 8 samples comprised of 6 positive samples and 2 negative samples were used in this study for comparative evaluation with RT-PCR. Thus, due to easy operation without a requirement of sophisticated equipment and skilled personnel, the RT-LAMP assay reported here is extremely rapid, cost-effective, highly sensitive, and specific and has potential usefulness for rapid detection of NPEV.